INVESTIGATION OF PREDATOR–PREY RELATIONSHIPS OF BLACKTIP REEF SHARKS AT CHAGAR HUTANG TURTLE SANCTUARY USING STABLE ISOTOPE ANALYSIS - ZALINA BASHIR ALI (UNIVERSITI MALAYSIA TERENGGANU, 2022)
The predator–prey relationship between marine predators, such as sharks, and their prey is an important association which helps to control the flow of nutrients and energy through the marine ecosystem and mediate the dynamics and structures of marine communities. To effectively preserve ecosystem balance and resilience in marine habitats, conservation measures must encompass holistic approaches which involve the protection of multiple species simultaneously. This makes it important to understand how different species interact and influence each other. The present study investigated the predator–prey interactions between blacktip reef sharks and their prey in Chagar Hutang Bay on Redang Island, Terengganu with special emphasis on their predation of turtle hatchlings. Stable isotope analysis (SIA) and stomach content observations were used to determine the proportional dietary compositions of the sharks at different times during the year, revealing the relative contributions of turtle hatchlings and other prey to the sharks’ diets.